STRATEGI UNTUK MENINGKATKAN KOMPETENSI DAN DAYA SAING ORGANISASI - Prasetyo, Sunu Herdi; Faeni, Dewi Puspaningtyas (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This study investigates the influence of cooperative management strategies and service quality on members’ welfare, with member participation as a mediating variable, in Koperasi Dwi Cakti Bhakti Puspalad. A quantitative research design was adopted, employing path analysis to examine causal relationships among the variables. The population consisted of all active cooperative members with at least one year of membership, ensuring sustained involvement in cooperative activities. The findings indicate that both management strategies and service quality positively and significantly affect members’ welfare, both directly and indirectly through enhanced member participation. These results underscore the importance of strategic collaboration among cooperative management, members, and supervisory institutions to optimize the role of military-based cooperatives in promoting economic empowerment and welfare. The study provides practical implications for designing adaptive, sustainability-oriented cooperative management models suitable for military contexts. This research contributes to the literature by empirically confirming the mediating role of member participation in enhancing member welfare.